To what extent are African education policies pro-poor? - (:unkn) unknown (My University, 2004)
This paper discusses the distributive nature of education policies in developing countries, with a specific emphasis on sub-Saharan Africa. We show that human capital is particularly unequally distributed in sub-Saharan African countries and in Middle-East and North Africa and South Asian regions as well, after taking into account the inevitable (arithmetical) correlation which exists between the aggregate level of human capital and its concentration. We provide further evidence, based on sub-Saharan African schooling structure data, that these countries pay, relatively speaking, little attention to primary education, to the benefit of secondary education. We interpret this bias as the result of specific institutional characteristics of sub-Saharan Africa, which are deeply-rooted in its history (in particular its post-colonial legacy), its demography and its geography.
Keywords: African Research